Bezpieczeństwo i higiena pracy — pojęcie i odpowiedzialność - Wróbel, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article is foucsed on the whole concept, as well as the principles and legal provisions governing the issue of health and safety at work. The author comes to the conclusion, that health and safety at work is a indivisible conception — from a logical, substantial and legal point of view. Every person who performs work on any basis for instance: two types of appointment, election, contract of employment, cooperative contract of employment, agency agreement, contract of mandate has the right to healthy and safe work conditions. The person responsible for healthy and safe work conditions could be for example: employer, a person performing actions on behalf of an employer, member of a company’s management board in company, associate in registered partnership, proxy, liquidator, syndic, manager, works coordinator, inspector of National Labour Inspectorate, inspector of State Sanitary Inspection, social labour inspector. The responsibility regarding health and safety at work stems from the legal provisions provisions of health and safety at work, which are included in generally applicable provisions, and also from a specific kind of general clauses principles of health and safety at work.
Keywords: bezpieczeństwo i higiena pracy; pojęcie bezpieczeństwa i higieny; odpowiedzialność